ESTUDO E DEFINIÇÃO DE SENSORES PARA UM SISTEMA DE ANÁLISE DA QUALIDADE DA ENERGIA ELÉTRICA EM MÉDIA TENSÃO - Kinas, Jonathas R.; Hammarstron, Júlia R.; Carbonera, Luis F. B.; Campos, Mauricio d. (Salão do Conhecimento, 2013)
Resumo